Проектирование програмного модуля для исследования работы алгоритмов поисковых систем - Зосипов, В.В.; Булгакова, А.С. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2010)
This article discusses the principle of the software complex intended for the collection of values of external and internal factors of ranking websites to obtain the search and subsequent analysis of these data using the multilayered GMDH algorithm and its modifications. The analysis will identify the main factors taken into account by search engines when ranking websites, which will help us to estimate the effectiveness of search engines and further optimize the existing ranking algorithms.